The Influence of Product Innovation, Promotions, and Prices on the Decision to Purchase Oppo Brand Smartphones at the Aulia Ponsel Store Rantauprapat - Sitepu, Rehulina; Nasution, Meisa Fitri; Halim, Abd. (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The telecommunications business is very numerous and diverse nowadays, one of which is the smartphone sales business. OPPO brand smartphones are offered at low and medium prices for the lower and middle class, many are offered by agents, shops, and retailers, giving rise to increasingly tight competition among manufacturers. This research aims to determine and analyze the influence of product innovation, promotion, and price on purchasing decisions for OPPO brand smartphones at the Aulia Ponsel store in Rantauprapat. The method used in this research is associative research with quantitative techniques. The population in this study were all consumers at the Aulia Ponsel store in Rantauprapat, while the sample that met the observation sampling criteria was 316 people. Data collection techniques in this research used the Classical Assumption Test, Multiple Regression, t-test and F Test, and Coefficient of Determination. Data processing in this research using the SPSS version 25.0 software program was used to test the validity and reliability of the instruments and relationships hypothesized in the proposed theoretical model.